2010
DOI: 10.3174/ajnr.a2180
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Trial of Fluoroscopic Interlaminar Epidural Steroid Injection for Axial Low Back Pain: Effectiveness and Outcome Predictors

Abstract: BACKGROUND AND PURPOSE:An ESI for managing LBP is one of the most commonly performed interventions. The purpose of this observational study was to assess the effect of a therapeutic trial of a fluoroscopic interlaminar ESI for axial LBP and to analyze the outcome predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Although there is no high-quality ESI trial focused on degenerative neural foraminal stenosis alone, a small group of studies showed the effectiveness of transforaminal injection in patients with neural foraminal stenosis (37). For patients with axial low back pain, Lee et al (38) proposed a therapeutic trial of interlaminar ESI before discography when discogenic back pain is suspected.…”
Section: Indications Choice Of Approach and Contraindicationsmentioning
confidence: 99%
“…Although there is no high-quality ESI trial focused on degenerative neural foraminal stenosis alone, a small group of studies showed the effectiveness of transforaminal injection in patients with neural foraminal stenosis (37). For patients with axial low back pain, Lee et al (38) proposed a therapeutic trial of interlaminar ESI before discography when discogenic back pain is suspected.…”
Section: Indications Choice Of Approach and Contraindicationsmentioning
confidence: 99%
“…This assessment has been used previously by multiple authors. 18,19 There were some limitations in this study. Only a preinjection epidurography was noted, the post injection film could have shown improvement in contrast dispersion following the drug injection.…”
Section: Resultsmentioning
confidence: 90%
“…An intra-articular facet joint steroid injection was considered for patients presenting with the following: 1) severe low back pain [verbal numeric rating score (0-10) > 5.0]; 2) low back pain that was aggravated by position change including forward flexion and extension rotation; 3) focal tenderness in the paravertebral area in the lower lumbar level; and 4) low back pain without response after more than one month of conservative treatment, such as medication and physical therapy or persistent low back pain after a previous epidural steroid injection (21). year in our department (22,23).…”
Section: Patient Selectionmentioning
confidence: 99%